2020
DOI: 10.1177/1077558720954693
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Maryland’s Global Budgets on Medicare and Commercial Spending and Utilization

Abstract: In 2014, Maryland incorporated global budgets into its long-running all-payer rate-setting model for hospitals in order to improve health, increase health care quality, and reduce spending. We used difference-in-differences models to estimate changes in Medicare and commercial insurance utilization and spending in Maryland relative to a hospital-based comparison group. We found slower growth in Medicare hospital spending in Maryland than in the comparison group 4.5 years after model implementation and for comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Our results are consistent with findings from CMS’s final report for the MD model, which examined outcomes among commercial plan beneficiaries and identified a decline in commercial payer ED utilization 11,36 …”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with findings from CMS’s final report for the MD model, which examined outcomes among commercial plan beneficiaries and identified a decline in commercial payer ED utilization 11,36 …”
Section: Discussionsupporting
confidence: 89%
“…A common criticism of the MDAPM is that it is not generalizable beyond Maryland owing to the historical all-payer rate-setting system. 7,23 The findings of this study suggest that this rate-setting system was important in that it provided technical infrastructure to implement the model and a shared commitment to payer-agnostic hospital reimbursement. However, the study participants noted that one reason for successful MDAPM implementation was that it was designed for the unique circumstances in the state in collaboration with stakeholders from its inception.…”
Section: Discussionmentioning
confidence: 93%
“…Previously published findings on MDAPM impacts for the overall Medicare population found expenditure savings in total and for hospital services, reductions in hospital admissions, but no significant effects on ED visits, unplanned readmissions, or follow-up visits within 14 days after hospital discharge (Haber et al, 2019; Morrison et al, 2020). However, MDAPM impacts might not be uniform for all Medicare beneficiaries, and the present analyses found MDAPM impacts often differed among the subpopulations studied.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the increased interest in this payment strategy, global budgets are relatively new in the United States, and the research base on them is still developing. Previous studies have examined the impact of MDAPM on Medicare beneficiaries and found hospital expenditures declined under MDAPM primarily due to reductions for outpatient services (Beil et al, 2019; Haber & Beil, 2018; Morrison et al, 2020). Similarly, inpatient admissions declined, although emergency department (ED) visits increased slightly.…”
Section: Introductionmentioning
confidence: 99%